Empty ethics: the problem with informed consent - Corrigan, Oonagh (Sociology of health & illness, 2003)
Informed consent is increasingly heralded as an ethical panacea, a tool to counter autocratic and paternalistic medical practices. Debate about the implementation of informed consent is constricted and polarised, centring on the right of individuals to be fully informed and to freely choose versus an autocratic, paternalistic practice that negates individual choice. A bioethical framework, based on a principle‐led form of reductive/deductive reasoning, dominates the current model of informed consent. Such a model tends to the process of consent from its clinical and social setting. By fleshing out the social process involved when patients and healthy volunteer subjects consent to take part in clinical drug trials, this paper attempts to address the problem arising from the current ‘empty ethics’ model. My arguments are substantiated by qualitative interview data drawn from a study I conducted on the process of consent as experienced by participants in clinical drug trials.